2021
DOI: 10.1097/sle.0000000000000939
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of General, Epidural, and Spinal Anesthesia in Laparoscopic TEP (Total Extraperitoneal Repair) for Inguinal Hernia

Abstract: Purpose: Laparoscopic total extraperitoneal repair (TEP) is one of the most preferred minimally invasive methods for inguinal hernia repair. In our study, we aimed to compare the advantages and disadvantages of general anesthesia (GA), spinal anesthesia (SA), and epidural anesthesia (EA) for TEP operations.Materials and Methods: This is a retrospective study involving 221 patients who underwent TEP surgery for inguinal hernia between January 2018 and July 2020. Patients were divided into 3 groups as GA (n = 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
1
5
2
Order By: Relevance
“…In studies in the literature, the incidence of urinary retention in TEP surgeries performed with RA has been reported as 7.3% to 19.4%. 3,7,[26][27][28] In our study, urinary retention was observed in 7.2% of the SA group and 12.5% of group 2, similar to the literature, and no significant difference was found between the 2 groups (P = 0.477).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In studies in the literature, the incidence of urinary retention in TEP surgeries performed with RA has been reported as 7.3% to 19.4%. 3,7,[26][27][28] In our study, urinary retention was observed in 7.2% of the SA group and 12.5% of group 2, similar to the literature, and no significant difference was found between the 2 groups (P = 0.477).…”
Section: Discussionsupporting
confidence: 90%
“…In light of these factors, it has been reported in studies that patient satisfaction was found to be higher in the RA group. [3][4][5]24,26,27 In our study, although group 2 was higher than group 1 in terms of patient satisfaction, no significant difference was found between the 2 groups (P = 0.414).…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations